A KINEMATIC ANALYSIS OF THE VALVE TIMING MECHANISM WITH THREE ELEMENTS AND CONTINUOUS VALVE LIFT - Stelian MIHALCEA; Nicolae PANDREA (Fiabilitate şi Durabilitate)
An innovating solution for throttle-free load control for spark-ignition engines is variable valve timing system. In this paper is presented a kinematic analysis, using the analytic method, of the valve timing mechanism with three elements and continuous valve lift variation. It is also presented the numerical algorithm for the mechanism’s motion.